Realizing Gender Equality in Coastal Areas: Conservation of Critical Land and Empowerment of Women - Simarmata, Kisvan; Widhagdha, Miftah Faridl; Pradipta, Ganuardi; Aditya, Rahadiyand; Saipullah (Asean Social Work Journal, 2023)
The conversion of mangroves into shrimp ponds occurred in the coastal area of Kampung Beting, Pantai Bahagia Village, Bekasi Regency, West Java Province, Indonesia, in the period 1990–2010. High income from shrimp ponds makes people ignore the ecological functions of mangrove forests, one of which is to prevent abrasion. However, since 2010, the destruction of hundreds of hectares of mangrove forests, worsened by climate change that hits almost the whole world, especially island countries like Indonesia, has submerged the shrimp ponds in Pantai Bahagia Village with sea water. Now, not only the shrimp ponds as their major income have disappeared, but also their living space is also threatened by severe abrasion. Gender inequality and the marginalized role of coastal women also make the socio-economic conditions of the community become worse. This study observes the role of women in Pantai Bahagia Village in responding to environmental and socio-economic problems in their area. This study uses a phenomenological approach, data is collected through observation, interviews, and documentation. The results of the study show that women's empowerment plays a role in conserving critical land. Women's responses to environmental problems in their area include: 1) creating changes in women's awareness and behavior as an effort to repair and restore damaged mangrove land, and 2) carrying out activities to protect mangrove plants. Women's responses to socio-economic problems include 1) women's active involvement in productive economic activities 2) Utilization of non-timber mangrove products in processed food and crafts. Finally, this study recommends a concept to address critical coastal land issues, namely by involving women in various activities, both nature conservation and empowerment activities.